Parameters affecting fluidized motion conveying of fly ash - Gupta S.K.; Agarwal V.K.; Singh S.N.; Seshadri V.; Mills D. (My University, 2025)
A fluidized motion conveying system (FMCS) that conveys particulate material over a distance of 7.5m was developed to investigate the influence of operating parameters on the material mass flow rate and bed depth. The effect of channel length (varied over 7.5m, 5.5m, and 3.7m) was also investigated in relation to the observed variables. It is found that, for a given superficial air velocity, increase in conveying distance reduces the channel conveying capacity at all conveyor inclinations. The effect of superficial air velocity and channel inclination on material mass flow rate and bed depth, however, remains the same as reported earlier for 3.7m channel length. The predicted material mass flux and operating superficial air velocity did not agree with the experimental data, thus, the empirical relations applicable to the design of air gravity conveyors for optimum yield were not valid for the design of FMCS.